2004
DOI: 10.1086/502956
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Alcohol-Based Handrub and Quality Improvement Interventions to Improve Hand Hygiene in a Russian Neonatal Intensive Care Unit

Abstract: EDITORIAL 191Pseudomonas cepacia infection associated with chlorhexidine contamination. Am J Med 1982;73:183-186

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…9 Some reports of short-term im-provements in compliance that occurred after the introduction of alcohol-based hand rubs, often recorded from overt observation, have been published. [10][11][12][13] Although the benefits of the interventions reported by Pittet et al 7 and Larson et al 8 are undoubted and the costeffectiveness of the programs has been justified, 14 we must now identify why these interventions were successful. Handwashing as a practice is a globally recognized phenomenon; however, the inability to motivate HCW compliance with handwashing guidelines suggests that handwashing behavior is complex.…”
mentioning
confidence: 99%
“…9 Some reports of short-term im-provements in compliance that occurred after the introduction of alcohol-based hand rubs, often recorded from overt observation, have been published. [10][11][12][13] Although the benefits of the interventions reported by Pittet et al 7 and Larson et al 8 are undoubted and the costeffectiveness of the programs has been justified, 14 we must now identify why these interventions were successful. Handwashing as a practice is a globally recognized phenomenon; however, the inability to motivate HCW compliance with handwashing guidelines suggests that handwashing behavior is complex.…”
mentioning
confidence: 99%
“…Antibiotics usage reduced as a result of the decreased infection rate. 35 Meta-analysis using a random effects model indicated that a range of strategies, such as educational campaigns, musical parodies, reminders, easy access to hand hygiene sanitizers, UV sensors and performance feedback, improved HHC [odds ratio (OR)2.04; 95% confidence interval (CI) 1.40, 2.97]. Studies which specifically provided performance feedback at either the individual or group levels reported a more significant improvement in HHC compared to those who did not participate in the study (OR 2.81; 95% CI 1.32, 5.96 vs. OR 1.55; 95% CI 1.13-2.11).…”
Section: Hand Hygienementioning
confidence: 99%